Pipistrellus (Pipistrellus) kuhlii - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Pipistrellus (Pipistrellus) kuhlii (Kuhl 1817) [Vespertilio] kuhlii Kuhl 1817, Die Deutschen Fledermause. Hanau: 14. Type Locality: Italy, Friuli-Venezia Giulia, Trieste. Vernacular Names: Kuhl's Pipistrelle. Synonyms: Pipistrellus (Pipistrellus) calcarata Gray 1838. Subspecies:: Subspecies Pipistrellus (Pipistrellus) kuhlii subsp. kuhlii Kuhl 1817 Subspecies Pipistrellus (Pipistrellus) kuhlii subsp. ikhwanius Cheesman and Hinton 1924 Subspecies Pipistrellus (Pipistrellus) kuhlii subsp. lepidus Blyth 1845 Distribution: C Europe, Near East through the Caucasus to Kazakhstan and Pakistan; SW Asia. Conservation: IUCN 2003 and IUCN / SSC Action Plan (2001) – Lower Risk (lc). Discussion: Subgenus Pipistrellus . Does not include African populations (here referred to hesperidus ), see Kock (2001 b ). Canary Isls populations referred to kuhlii by Pestano et al. (2003) probably also represent hesperidus and also listed under that taxon. Reviewed in part by Harrsion and Bates (1991) and Bates and Harrison (1997). For discussion of correct spelling ( kuhlii ) and authorship (Kuhl not Natterer), see Bogdanowicz and Kock (1998). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Chiroptera - Family Vespertilionidae, pp. 451-529 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 476, DOI: 10.5281/zenodo.7316519